Processing affects beta-casomorphin peptide formation during simulated gastrointestinal digestion in both A1 and A2 milk. (October 2021) - Lambers, Tim T.; Broeren, Sjef; Heck, Jeroen; Bragt, Marjolijn; Huppertz, Thom
Abstract: Variation between bovine A1-or A2-type β-caseins are suggested to affect beta-casomorphin-7 (BCM-7) formation, which may affect health. Studies assessing BCM-7 formation often use raw milk, but processing of milk is known to affect digestion. Using in vitro digestion and stable-isotope assisted peptide quantification, we reveal that BCM-7 is formed under intestinal conditions from both A1-and A2-type milk. Moreover, formation of BCM-7 was affected by industrial relevant heating in both A1 and A2 milk. Further studies with a large number of single A1-and A2-type cows are needed to elaborate if amounts of BCM-7 formed are different between A1 and A2 milk. Both longer and shorter BCM peptide sequences that may display similar activities should be taking into account as a longer BCM-7 containing peptide (BCM-7 +2) could also be detected in A2 milk intestinal digesta.